Wastes in the ocean v.1 industrial and sewage wastes in the ocean. - Duedall, Iver W.; Ketchum, Bostwick H.; Park, P. Kilho; Kester, Dana R. (John Wiley & Sons, Inc., 1983)
A Wiley-Interscience publication. Wastes in the ocean; v. 1. Environmental science and technology